Perencanaan Proyek Struktur Semi Gantry Crane Menggunakan Critical Chain Project Management - M. Faiizuddaroini; Wahyu Nugroho; Supriyadi Supriyadi; Ahmad Nalhadi (Universitas Mercu Buana, 2022)
Project completion work has problems related to project completion not being on time, thereby increasing costs and resources. The work on the gantry crane structure includes projects that experience problems related to incompatibility between project planning and actual project work. This study aims to plan project activities by speeding up processing time and providing prevention strategies to minimize project delays. This study uses the critical chain project management method using the cut & paste method by 30%. The results showed the total buffer time was ten days, consisting of eight project buffer days and two feeding buffer days. The total time for the semi-gantry crane structure project has accelerated from 43 days to 33 days. Suggestions for prevention that can be done to complete the project according to the plan are adding project workers, adding tools or machines, and eliminating multitasking activities that cause project workers not to finish their work immediately.